2020
DOI: 10.2147/ott.s268635
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genetic and Clinical Characterization of HOXB2 in Glioma</p>

Abstract: Background: Glioma is a highly aggressive and heterogeneous cancer with poor survival rates. Homeobox (HOX) genes are transcription factors that play pivotal roles in many aspects of cellular physiology, embryonic development, and tissue homeostasis. Mutations in HOX genes can lead to increased cancer predisposition. Abnormal expression of HOXB2 may result in the development and progression of tumors. However, its prognostic value and mechanism of dysregulation remain unclear. Methods: The present study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In glioma, homeobox B2 (HOXB2) is an independent prognostic marker. HOXB2 is related to the invasion and proliferation of glioma cells in vitro, and has a certain effect on the invasion of glioma cells (5). We examined the regulatory role of the SP1/LINC00339/miR-378a-3p/ MED19 axis in colorectal cancer, and provided new insights into the molecular mechanism of colorectal cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…In glioma, homeobox B2 (HOXB2) is an independent prognostic marker. HOXB2 is related to the invasion and proliferation of glioma cells in vitro, and has a certain effect on the invasion of glioma cells (5). We examined the regulatory role of the SP1/LINC00339/miR-378a-3p/ MED19 axis in colorectal cancer, and provided new insights into the molecular mechanism of colorectal cancer (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the esophageal squamous cell carcinoma, Sox-6 was reported as a tumor suppressor gene 47 whereas Sox-6 was shown to possess a strong oncogenic property in Ewing sarcoma 48 . In addition, other cancer-related TFs were also found in our enrichment analysis, including ALX3 (in neuroblastoma) 49 , HOXA6 (in clear renal cell carcinoma) 50 , HOXC-8, FOXO1 (in breast cancer) 51 , 52 , PARP (in neuroblastoma, endometrial cancer, breast cancer, and malignant lymphoma) 53 56 , IPF1 (in pancreatic neuroendocrine neoplasms) 57 , and HOXB2 (in glioma) 58 . Therefore, by focusing on germline TE insertions following identification of OS patient-specific TE insertions, we revealed the typically overlooked importance of germline TE insertions in the development of OS.…”
Section: Discussionmentioning
confidence: 60%
“…another study demonstrated that HoXB2 promoted the invasion of HoP-62 non-small cell lung cancer (nSclc) cells via transcriptionally regulating the expression of metastasis-related genes (27). in addition, HoXB2 promoted glial cell proliferation and invasion in vitro in 1,001 patients with glioma, and it was positively correlated with tumor grade and established as an independent prognostic biomarker (28). However, the effects of HoXB2 and nuSaP1 on the proliferation, invasion and migration of nephroblastoma cells remain unclear.…”
Section: Discussionmentioning
confidence: 99%